IGF-1 Receptor and Adhesion Signaling: An Important Axis in Determining Cancer Cell Phenotype and Therapy Resistance - Cox, Orla T.; O’Shea, Sandra; Tresse, Emilie; Bustamante-Garrido, Milan; Kiran-Deevi, Ravi; O’Connor, Rosemary (Frontiers in Endocrinology, 2015)
IGF-1R expression and activation levels generally cannot be correlated in cancer cells, suggesting that cellular proteins may modulate IGF-1R activity. Strong candidates for such modulation are found in cell-matrix and cell-cell adhesion signaling complexes. Activated IGF-1R is present at focal adhesions, where it can stabilize β1 integrin and participate in signaling complexes that promote invasiveness associated with epithelial mesenchymal transition (EMT), and resistance to therapy. Whether IGF-1R contributes to EMT or to non-invasive tumor growth may be strongly influenced by the degree of ECM engagement and the presence or absence of key proteins in IGF-1R-cell adhesion complexes. One such protein is PDLIM2, which promotes both cell polarization and EMT by regulating the stability of transcription factors including NFκB, STATs and beta catenin. PDLIM2 exhibits tumor suppressor activity, but is also highly expressed in certain invasive cancers. It is likely that distinct adhesion complex proteins modulate IGF-1R signaling during cancer progression or adaptive responses to therapy. Thus, identifying the key modulators will be important for developing effective therapeutic strategies and predictive biomarkers.